Pembangunan Ekonomi Melalui Peningkatan Ketahanan dan Kemandirian Masyarakat Di Desa Sindangsari Kecamatan Kutawaluya Kabupaten Karawang - Gumilar, Gun Gun; Hilmi, Indah Laily; Wulandari, Yulia Eka; Annisa, Windy (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Karawang Regency is one of the areas that have a fairly high income. However, in 2021 Karawang Regency is designated as an extremely poverty area with a percentage of an extremely poor population of 4.51% with reference to data from the Central Agency on Statistics (BPS). One of the villages that have become a priority for extreme poverty alleviation programs in Karawang Regency is Sindangsari Village. Therefore, to assist the government in improving the economy of Sindangsari Village, Community Service activities are carried out. This Community Service activity is carried out by initiating the empowerment of village officials and the community in improving the economy. Sindangsari Village, Kutawaluya District, Karawang Regency through the submission of the legality of Usaha Mikro, Kecil dan Menengah (UMKM) in the form of a Business Identification Number (NIB) and halal certificates, the creation of a website as a means of promoting UMKM, as well as seminar activities to encourage the revitalization of BUMDes. The method used in the service consists of 3 (three) stages, which consist of: 1) preparation; (2) implementation; (3) reporting. All community service programs have shown success and can be used as a reference to improve village economic development, namely the realization of making business legalities as many as 50 UMKM, making village websites, and seminars on increasing the capability of village apparatus and BUMDes management. However, the success of the service program must be accompanied by increased synergy between village officials and the community to strengthen village independence.